Cardiac biomarkers and association with subsequent cardiomyopathy and mortality among adult survivors of childhood cancer: A report from the St. Jude Lifetime Cohort. Issue 3 (27th October 2020) - Dixon, Stephanie B.; Howell, Carrie R.; Lu, Lu; Plana, Juan C.; Joshi, Vijaya M.; Luepker, Russell V.; Durand, Jean B.; Ky, Bonnie; Lenihan, Daniel J.; Jefferies, John L.; Green, Daniel M.; Ehrhardt, Matthew J.; et al.
Abstract : Background: Survivors of childhood cancer exposed to cardiotoxic therapies are at significant cardiovascular risk. The utility of cardiac biomarkers for identifying the risk of future cardiomyopathy and mortality is unknown. Methods: N‐terminal pro–B‐type natriuretic peptide (NT‐proBNP) and cardiac troponin T (cTnT) were assessed in 1213 adults 10 or more years from a childhood cancer diagnosis; 786 were exposed to anthracycline chemotherapy and/or chest‐directed radiation therapy (RT). NT‐proBNP values above age‐ and sex‐specific 97.5th percentiles were considered abnormal. Generalized linear models estimated cross‐sectional associations between abnormal NT‐proBNP and anthracycline or chest RT doses as risk ratios with 95% confidence intervals (CIs). A Poisson distribution estimated rates and a Cox proportional hazards model estimated hazard ratios (HRs) for future cardiac events and death. Results: At a median age of 35.5 years (interquartile range, 29.8‐42.5 years), NT‐proBNP and cTnT were abnormal in 22.5% and 0.4%, respectively. Exposure to chest RT and exposure to anthracycline chemotherapy were each associated with a dose‐dependent increased risk for abnormal NT‐proBNP ( P for trend <.0001). Among exposed survivors with no history of Common Terminology Criteria for Adverse Events–graded cardiomyopathy and with normal systolic function, survivors with abnormal NT‐proBNP had higher rates per 1000 person‐years of cardiac mortality (2.93 vs 0.96; P < .0001) and future cardiomyopathy (32.10 vs 15.98; P < .0001) and an increased risk of future cardiomyopathy (HR, 2.28; 95% CI, 1.28‐4.08) according to a multivariable assessment. Conclusions: Abnormal NT‐proBNP values were prevalent and, among survivors who were exposed to cardiotoxic therapy but did not have a history of cardiomyopathy or current systolic dysfunction, identified those at increased risk for future cardiomyopathy. Further longitudinal studies are needed to confirm this novel finding. Abstract : In this longitudinal cohort study including 1213 adult survivors of childhood cancer, nearly 25% have an abnormal N‐terminal pro–B‐type natriuretic peptide (NT‐proBNP) value for age and sex at the baseline. Among survivors exposed to cardiotoxic therapy who have a normal ejection fraction at the baseline, those with an abnormal NT‐proBNP value have more than twice the risk of future cardiomyopathy; this is a significant finding.